Preparation method and application of molecular imprinted photoelectrochemical sensor based on light-excited nanozyme

By preparing a molecularly imprinted polymer film on the surface of carbon-doped TiO2 nanozyme and modifying it onto the electrode, a molecular imprinted photoelectrochemical sensor based on photoexcited nanozymes was formed, which solved the problems of narrow detection range and low sensitivity in the prior art, and achieved high sensitivity and specific detection of norfloxacin.

CN119044287BActive Publication Date: 2025-04-29EAST CHINA JIAOTONG UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411166551.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2025-04-29
Estimated Expiration
2044-08-23

AI Technical Summary

Technical Problem

In the prior art, the application of carbon-doped TiO2 nanoenzymes in the field of analytical sensing has problems with narrow detection range and low sensitivity, and lack of specific binding sites, which makes it difficult to achieve selective detection of substrates.

Method used

Using the preparation method of a molecularly imprinted photoelectrochemical sensor based on photoexcited nanozymes, a titanium metal organic framework compound is synthesized by using isopropyl titanate as the titanium source and 2-aminoterephthalic acid as the ligand, and carbon-doped TiO2 is obtained by low-temperature hydrolysis. A molecular imprinted polymer film is then prepared on its surface and modified onto the base electrode to form a molecular imprinted photoelectrochemical sensor based on photoexcited nanozymes.

Benefits of technology

High sensitivity and specific detection of quinolones such as norfloxacin is achieved, and the catalytic performance of nanoenzymes is regulated through photoexcitation, which reduces the background signal and improves the accuracy and sensitivity of the detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119044287B_ABST
    Figure CN119044287B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a molecularly imprinted photoelectrochemical sensor based on photoexcited nanozyme, belonging to the technical fields of chemical sensing and electroanalytical chemistry detection. In the invention, carbon-doped TiO2 is prepared by using a metal-organic framework as a sacrificial precursor, and then, taking the carbon-doped TiO2 as a photoexcited nanozyme, a molecularly imprinted polymer film is prepared on the surface thereof and then used to modify a basic electrode, so as to obtain the molecularly imprinted photoelectrochemical sensor based on the photoexcited nanozyme. The molecularly imprinted photoelectrochemical sensor based on the photoexcited nanozyme constructed by combining photoelectrochemical detection, a molecularly imprinted polymer and a carbon-doped TiO2 nanozyme with high catalytic activity can realize highly sensitive and highly selective detection of a substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of chemical sensing and electroanalytical chemical detection, and in particular to a preparation method and application of a molecular imprinting photoelectrochemical sensor based on light-excited nanozyme. Background Art

[0002] Natural enzymes have high selectivity and high catalytic activity, and are widely used in clinical diagnosis, food industry, sensors and other fields. However, the inherent defects of natural enzymes (such as high cost, low stability, difficulty in large-scale production, etc.) greatly limit their practical applications. In order to overcome the defects of natural enzymes, the research and development of artificial enzyme mimics that are stable and can be synthesized at low cost has attracted increasing attention from researchers. Among them, nanozymes, that is, nanomaterials with enzyme-like catalytic activity, are a new type of enzyme mimics. Compared with natural enzymes, nanozymes have many advantages such as high stability, easy large-scale production, and adjustable activity, and have important application prospects. In particular, peroxide nanozymes can catalyze hydrogen peroxide to oxidize some reducing substrates and are widely used in the field of analytical sensing.

[0003] Similar to natural peroxidase, peroxidase nanozymes need the participation of hydrogen peroxide to exert their catalytic performance. H2O2 electron acceptors are unstable and easily decomposed, which will lead to an increase in the background signal of the system, thereby reducing the catalytic ability of the nanozymes. Using light instead of H2O2 as the excitation source of peroxidase nanozymes can effectively overcome the instability and easy decomposition of H2O2. Light replaces H2O2 to produce reactive oxygen species, such as O2 · and ·OH as oxidants to oxidize the substrate and can be controlled by simple light irradiation, which provides great convenience for regulating the catalytic activity of the nanozyme.

[0004] In order to achieve the photoexcitation response of peroxidase-like nanozymes, materials with photoresponse and nanozyme catalytic properties are effective candidates. Nano-titanium dioxide, a typical semiconductor material, has been reported to have peroxidase-like catalytic activity and has been used in the field of analytical sensing, but its wide bandgap limits its application in the visible light field. Carbon doping of TiO2 regulates the valence band and band gap of TiO2 by affecting the O 2p orbital, forming an intermediate energy level above the top of the O 2p valence band, which extends the photoresponse range of TiO2 from the ultraviolet region to the visible region and promotes electron-hole separation. The doped TiO2 exhibits more excellent photoelectrochemical properties.

[0005] At present, sol-gel, hydrothermal synthesis, high temperature annealing TiO2-carbon materials and other methods have been used to prepare carbon-doped TiO2 materials. However, these methods require high temperature treatment and external carbon source, as well as complex preparation processes. Moreover, the obtained carbon-doped TiO2 has a low specific surface area and low photocatalytic activity. In addition, carbon-doped TiO2 nanozymes lack specific binding sites, and any substrate that diffuses to its surface may react. The introduction of molecular imprinting polymers as specific recognition elements of nanozymes can effectively solve the problem of the lack of selectivity of light-excited peroxide nanozymes for substrates.

[0006] At present, carbon-doped TiO2 nanozymes are widely used in the field of analytical sensing. However, the current literature reports are mainly limited to colorimetric sensing applications. Colorimetric sensing has defects such as narrow detection range and low sensitivity. Therefore, it is necessary to explore new detection technologies and couple them with highly catalytically active carbon-doped TiO2 nanozymes to achieve highly sensitive sensing applications of nanozymes.

[0007] Norfloxacin is an important synthetic quinolone antibiotic with good antibacterial effect. It is widely used in aquaculture, animal husbandry and human disease treatment. After norfloxacin enters the organism, about 70% is excreted as the original drug or incompletely metabolized products, and then enters the environmental system, polluting the ecological environment. Norfloxacin in the environmental system will induce microorganisms in the environment to produce drug-resistant genes, enter the human body through the food chain, and seriously endanger human health. Therefore, the detection of quinolone antibiotics is of great significance. If the new detection technology can be coupled with the highly catalytically active carbon-doped TiO2 nanozyme, the development of new equipment and methods that can detect quinolone antibiotics such as norfloxacin with high sensitivity will have broad application prospects. Summary of the invention

[0008] The purpose of the present invention is to provide a preparation method and application of a molecular imprinting photoelectrochemical sensor based on light-excited nanozymes to solve the problems existing in the above-mentioned prior art. The present invention combines the catalytic performance of carbon-doped TiO2 light-excited nanozymes, the high selectivity of molecular imprinting polymers, and the high sensitivity of photoelectrochemical detection, and can detect norfloxacin sensitively, accurately, and specifically. The present invention uses light as an excitation source to excite the nanozymes, and the catalytic performance of the simulated enzyme can be freely regulated by turning the light off or on.

[0009] To achieve the above object, the present invention provides the following solutions:

[0010] One of the technical solutions of the present invention: a method for preparing a molecular imprinting photoelectrochemical sensor based on light-excited nanozymes, comprising the following steps:

[0011] A titanium metal organic framework compound is synthesized using isopropyl titanate as a titanium source and 2-aminoterephthalic acid as a ligand; the titanium metal organic framework compound is subjected to low-temperature hydrolysis to obtain carbon-doped TiO2; a carbon-doped TiO2 / molecular imprinting polymer film is prepared by chemical polymerization using the carbon-doped TiO2 and a template molecule (i.e., a molecular imprinting polymer film is synthesized on the surface of the carbon-doped TiO2); the carbon-doped TiO2 / molecular imprinting polymer film is fixed to the surface of a base electrode to obtain the molecular imprinting photoelectrochemical sensor based on light-excited nanozymes.

[0012] 2-Aminoterephthalic acid with an amino auxochromophore absorbs in the visible light region, and using it as a ligand can effectively prepare metal organic framework compounds and their derivatives having photocatalytic properties in the visible light region.

[0013] Furthermore, the method of synthesizing a titanium metal organic framework compound using isopropyl titanate as a titanium source and 2-aminoterephthalic acid as a ligand includes: mixing 2-aminoterephthalic acid, dimethylformamide, methanol and isopropyl titanate, reacting at 60-250°C for 5-50h, and after the reaction, soaking the reactants in dimethylformamide for 6-40h, then washing and drying to obtain the titanium metal organic framework compound; the dosage ratio of the 2-aminoterephthalic acid, dimethylformamide, methanol and isopropyl titanate is 20-1500mg:5-150mL:0.5-50mL:50-1500μL.

[0014] Furthermore, the washing includes: first washing with ethanol and centrifuging, then washing with a mixed solution of water and ethanol and centrifuging, and finally washing twice with water and then centrifuging.

[0015] Furthermore, the temperature of the low-temperature hydrolysis is 50-200° C., and the time is 10-72 hours; the low-temperature hydrolysis is carried out in a mixed solution of dimethylformamide and water.

[0016] Furthermore, the low-temperature hydrolysis of the titanium metal organic framework compound to obtain carbon-doped TiO2 includes: mixing the titanium metal organic framework compound with dimethylformamide and water, and performing a low-temperature hydrolysis reaction at 50-200°C for 10-72 hours. After the reaction is completed, the reactant is washed and dried to obtain carbon-doped TiO2. The washing includes first washing with a mixed solution of water and ethanol, centrifuging 3 times, and then washing with water and centrifuging 3 times. The drying temperature is 40-150°C and the time is 3-20 hours.

[0017] Furthermore, the method of preparing a carbon-doped TiO2 / molecular imprinting polymer film by chemical polymerization using carbon-doped TiO2 and template molecules includes: mixing carbon-doped TiO2, template molecules, methacrylamide and ethanol, ultrasonicating until completely dissolved, prepolymerizing for 5-40 hours, then adding ethylene glycol dimethacrylate and 2,2′-azobisisobutyronitrile, stirring for 10-60 minutes and reacting at 30-85°C for 10-40 hours, washing, drying and eluting in a sodium hydroxide solution for 5-90 minutes after the reaction to obtain the carbon-doped TiO2 / molecular imprinting polymer film; the amount ratio of the carbon-doped TiO2, template molecules, methacrylamide, ethanol, ethylene glycol dimethacrylate and 2,2′-azobisisobutyronitrile is 20-500 mg: 10-120 mg: 10-200 mg: 10-100 mL: 20-300 μL: 10-100 mg.

[0018] Furthermore, the concentration of the sodium hydroxide solution is 0.05-0.25 mol / L.

[0019] Furthermore, the washing is performed by centrifugation with ethanol; the drying temperature is 40-100°C and the drying time is 5-15h.

[0020] Furthermore, the method of fixing the carbon-doped TiO2 / molecular imprinting polymer film to the surface of the base electrode to obtain the molecular imprinting photoelectrochemical sensor based on light-excited nanozyme includes: dispersing the carbon-doped TiO2 / molecular imprinting polymer film in water to obtain a carbon-doped TiO2 / molecular imprinting polymer film dispersion; mixing the carbon-doped TiO2 / molecular imprinting polymer film dispersion with ethanol and perfluororesin solution to obtain a mixed dispersion; drop-coating the mixed dispersion on the surface of the base electrode, and obtaining a base electrode modified with the carbon-doped TiO2 / molecular imprinting polymer film after drying, which is the molecular imprinting photoelectrochemical sensor based on light-excited nanozyme.

[0021] Furthermore, the concentration of the carbon-doped TiO2 / molecularly imprinted polymer membrane dispersion is 2-20 mg / mL; the concentration of the perfluororesin solution is 1-10 wt %; and the volume ratio of the carbon-doped TiO2 / molecularly imprinted polymer membrane dispersion, ethanol and perfluororesin solution is 50-500:50-500:10-200.

[0022] Furthermore, the template molecule is norfloxacin.

[0023] Furthermore, the base electrode is a glassy carbon electrode.

[0024] Furthermore, the diameter of the glassy carbon electrode is 3 mm.

[0025] Furthermore, the mixed dispersion is dripped on the base electrode in an amount of 2-20 μL.

[0026] Further preferably, the template molecule is norfloxacin, and the preparation method includes more specific steps (preparation process as shown in Figure 1 shown):

[0027] (1) adding 20-1500 mg of 2-aminoterephthalic acid to a polytetrafluoroethylene liner of a high-pressure reactor, then adding 5-150 mL of dimethylformamide and 0.5-50 mL of methanol, and dissolving by ultrasonication; then adding 50-1500 μL of isopropyl titanate, stirring rapidly until a paste is formed, and then transferring to a high-pressure reactor, reacting at 60-250° C. for 5-50 h, and after the reaction is completed, soaking the reactant in dimethylformamide for 6-40 h, then washing with ethanol, centrifuging, then washing with a mixed solution of water and ethanol, centrifuging, and finally washing with water twice, centrifuging, and drying to obtain a titanium metal organic framework compound;

[0028] (2) adding 20-600 mg of the titanium metal organic framework compound to the polytetrafluoroethylene liner of the autoclave, adding 3-75 mL of dimethylformamide and 1-25 mL of water, ultrasonicating until completely dissolved, and then hydrolyzing in the autoclave at 50-200° C. for 10-72 h. After the reaction, washing the reactant with a mixed solution of water and ethanol, centrifuging it 3 times, and then washing it with water, centrifuging it 3 times; and then drying it under vacuum conditions at 40-150° C. for 3-20 h to obtain the carbon-doped TiO2;

[0029] (3) 20-500 mg carbon-doped TiO2, 10-120 mg norfloxacin, 10-200 mg methacrylamide, and 10-100 mL ethanol are sequentially added to a beaker, and then ultrasonicated until completely dissolved, followed by stirring at room temperature for 5-40 h for prepolymerization, and then 20-300 μL ethylene glycol dimethacrylate and 10-100 mg 2,2′-azobisisobutyronitrile are added, stirred for 10-60 min, and then placed in a 30-85° C. water bath, heated at a constant temperature for 10-40 h, washed with ethanol, centrifuged, and then dried in a 40-100° C. vacuum drying oven for 5-15 h to obtain a carbon-doped TiO2 / molecularly imprinted polymer film-norfloxacin;

[0030] (4) placing the carbon-doped TiO2 / molecularly imprinted polymer membrane-norfloxacin in a 0.05-0.25 mol / L sodium hydroxide solution for elution for 5-90 min, and obtaining a carbon-doped TiO2 / molecularly imprinted polymer membrane after eluting the norfloxacin;

[0031] (5) Using water as a dispersant to prepare a 2-20 mg / mL carbon-doped TiO2 / molecularly imprinted polymer film dispersion, 50-500 μL of the carbon-doped TiO2 / molecularly imprinted polymer film dispersion, 50-500 μL of ethanol, and 10-200 μL of a 1-10 wt% perfluororesin solution are mixed and ultrasonically dispersed to obtain a mixed dispersion; taking 2-20 μL of the mixed dispersion, applying a drop of the mixed dispersion to the surface of a clean L-shaped glassy carbon electrode (with a diameter of 3 mm), and drying it to obtain a carbon-doped TiO2 / molecularly imprinted polymer film modified glassy carbon electrode, which is a molecularly imprinted photoelectrochemical sensor based on light-excited nanozymes for determining norfloxacin.

[0032] The second technical solution of the present invention: a molecular imprinting photoelectrochemical sensor based on light-excited nanozyme prepared by the above-mentioned preparation method.

[0033] The third technical solution of the present invention: Application of the above-mentioned molecular imprinting photoelectrochemical sensor based on light-excited nanozyme in the detection of norfloxacin.

[0034] Furthermore, the molecular imprinting photoelectrochemical sensor based on light-excited nanozymes (i.e., carbon-doped TiO2 / molecularly imprinted polymer film modified glassy carbon electrode) is used as the working electrode, the Ag / AgCl electrode is used as the reference electrode, and the platinum electrode is used as the auxiliary electrode to form a three-electrode system to achieve photoelectrochemical detection of norfloxacin.

[0035] Furthermore, the base solution of the three-electrode system is a mixed aqueous solution containing 1.8 mmol / L hydroquinone and 0.1 mol / L sodium sulfate solution.

[0036] Furthermore, the detection step specifically includes:

[0037] The molecular imprinting photoelectrochemical sensor based on light-excited nanozyme is incubated in norfloxacin standard solutions of different concentrations, the molecular imprinting photoelectrochemical sensor based on light-excited nanozyme incubated with norfloxacin standard solutions of different concentrations is subjected to photoelectrochemical test in a three-electrode system, the photocurrent response value is recorded, and a working curve is drawn according to the concentration of the norfloxacin standard solution and the photocurrent response value at the corresponding concentration; the molecular imprinting photoelectrochemical sensor based on light-excited nanozyme is incubated in a norfloxacin solution to be tested, the molecular imprinting photoelectrochemical sensor based on light-excited nanozyme incubated with the norfloxacin solution to be tested is subjected to photoelectrochemical test in a three-electrode system, the photocurrent response value is recorded, and the photocurrent response value corresponding to the norfloxacin solution to be tested is substituted into the working curve to obtain the concentration of the norfloxacin solution to be tested.

[0038] Furthermore, the concentrations of the norfloxacin standard solutions of different concentrations are 1.0, 5.0, 10.0, 20.0, 30.0, 40.0, and 50.0 μg / L, respectively.

[0039] Furthermore, the conditions of the photoelectrochemical test include: the light source is a 500W xenon lamp, the wavelength of the light source is ≥400nm, the light on-light off interval is 10s, and the potential is -0.2V.

[0040] The present invention discloses the following technical effects:

[0041] (1) The present invention first prepares carbon-doped TiO2 using a metal organic framework as a sacrificial precursor, then uses carbon-doped TiO2 as a photoexcited nanozyme, prepares a molecular imprinting polymer film on its surface, and then modifies the base electrode to obtain a molecular imprinting photoelectrochemical sensor based on photoexcited nanozyme. The carbon-doped TiO2 prepared using a metal organic framework as a sacrificial precursor has good catalytic activity. The introduction of molecular imprinting polymer as a specific recognition element of the nanozyme can effectively solve the problem of the lack of selectivity of the photoexcited peroxide nanozyme for the substrate. Due to the separation of the excitation signal (light) and the detection signal (current), the photoelectrochemical detection has the characteristics of low background signal and high sensitivity. Therefore, the present invention combines photoelectrochemical detection, molecular imprinting polymer and high catalytic activity carbon-doped TiO2 nanozyme to construct a molecular imprinting photoelectrochemical sensor based on photoexcited nanozyme, which can achieve high sensitivity and high selectivity detection of the substrate.

[0042] (2) The present invention uses isopropyl titanate as a titanium source and 2-aminoterephthalic acid as a ligand to synthesize a titanium metal organic framework compound, and uses it as a sacrificial precursor to prepare carbon-doped TiO2 by a low-temperature hydrolysis method. On the one hand, the use of a metal organic framework as a sacrificial precursor to prepare carbon-doped TiO2 can form a uniform element distribution, a large specific surface area, and highly dispersed active sites; on the other hand, the present invention prepares carbon-doped TiO2 by a low-temperature hydrolysis method, which is different from other methods such as high-temperature calcination methods in that it not only has low energy consumption, but also good stability and good batch repeatability of material preparation.

[0043] (3) The present invention uses a carbon-doped TiO2 / molecularly imprinted polymer film modified glassy carbon electrode as a working electrode, an Ag / AgCl electrode as a reference electrode, a platinum electrode as an auxiliary electrode, and a mixed aqueous solution containing 1.8 mmol / L hydroquinone and 0.1 mol / L sodium sulfate solution as a base liquid to form a three-electrode system. Due to the photoexcited nanozyme catalysis of carbon-doped TiO2 and the electron donor effect of hydroquinone, highly sensitive photoelectrochemical detection of norfloxacin can be achieved.

[0044] (4) The preparation method of the present invention has good universality and is not only applicable to the detection of norfloxacin, but can also be used to detect other substrates by simply changing the template molecule. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0046] Figure 1 The present invention is a flow chart for the preparation of a molecular imprinting photoelectrochemical sensor based on light-excited nanozymes.

[0047] Figure 2 These are scanning electron microscope images of the titanium metal organic framework compound and carbon-doped TiO2 with different hydrolysis times in Example 3, wherein A is the titanium metal organic framework compound (i.e., the hydrolysis time is 0 h); B is the carbon-doped TiO2 with a hydrolysis time of 12 h; C is the carbon-doped TiO2 with a hydrolysis time of 24 h; D is the carbon-doped TiO2 with a hydrolysis time of 36 h; E is the carbon-doped TiO2 with a hydrolysis time of 48 h; and F is the carbon-doped TiO2 with a hydrolysis time of 60 h.

[0048] Figure 3 This is the energy spectrum of carbon-doped TiO2 with a hydrolysis time of 48 h in Example 3, wherein A is the total element distribution diagram of C, O and Ti; B is the element distribution diagram of C; C is the element distribution diagram of O; and D is the element distribution diagram of Ti.

[0049] Figure 4 This is the X-ray diffraction pattern of carbon-doped TiO2 with a hydrolysis time of 48 h in Example 3.

[0050] Figure 5 It is the X-ray photoelectron spectrum of carbon-doped TiO2 with a hydrolysis time of 48 h in Example 3, wherein A is the full spectrum of carbon-doped TiO2; B is the high-resolution spectrum of C1s in carbon-doped TiO2; C is the high-resolution spectrum of O1s in carbon-doped TiO2; and D is the high-resolution spectrum of Ti2p in carbon-doped TiO2.

[0051] Figure 6 The catalytic performance of the titanium metal organic framework in Example 3 and the carbon-doped TiO2 nanozyme obtained by hydrolyzing the titanium metal organic framework for 48 hours, wherein A is the UV-visible spectrum of the titanium metal organic framework (with illumination); B is the UV-visible spectrum of the titanium metal organic framework (without illumination); C is the UV-visible spectrum of carbon-doped TiO2 (with illumination); D is the UV-visible spectrum of carbon-doped TiO2 (without illumination); E is the UV-visible spectrum of the color-developing substance 3,3′,5,5′-tetramethylbenzidine (with illumination).

[0052] Figure 7The catalytic performance of the carbon-doped TiO2 nanozyme obtained by hydrolyzing the titanium metal organic framework in Example 3 for different times.

[0053] Figure 8 3 and 4, respectively. The photocurrent response diagram of the molecular imprinting photoelectrochemical sensor of Example 3 to different concentrations of norfloxacin, wherein A is before incubation of norfloxacin; B is after incubation of 1.0 g / L norfloxacin; C is after incubation of 5.0 g / L norfloxacin; D is after incubation of 10.0 g / L norfloxacin; E is after incubation of 20.0 g / L norfloxacin; F is after incubation of 30.0 g / L norfloxacin; G is after incubation of 40.0 g / L norfloxacin; and H is after incubation of 50.0 g / L norfloxacin.

[0054] Fig. 9 This is a calibration curve of the photocurrent response of the molecular imprinting photoelectrochemical sensor of Example 3 to norfloxacin.

[0055] Fig.10 The mechanism exploration process and results of molecular imprinting photoelectrochemical sensor, where A is a 1.8 mmol L - 1 HQ and 0.1 mol L -1 A is the photocurrent diagram of a mixed aqueous solution of sodium sulfate; B is the photocurrent diagram when 0.1 mmol / L hydroxylamine hydrochloride is added to A; C is the photocurrent diagram when 0.1 mmol / L tryptophan is added to A; D is the photocurrent diagram when 0.1 mmol / L ethanol is added to A; E is the photocurrent diagram when 0.1 mmol / L thiourea is added to A.

[0056] Fig.11 The molecular imprinted photoelectrochemical sensor was prepared in the presence of 1.8 mmol L -1 HQ and 0.1 mol L -1 Photocurrent diagram of a mixed aqueous solution of sodium sulfate before and after deoxygenation.

[0057] Fig.12 Diagram of the catalytic mechanism of molecular imprinting photoelectrochemical sensor. DETAILED DESCRIPTION

[0058] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0059] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0060] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0061] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0062] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0063] Example 1

[0064] A preparation of a molecularly imprinted photoelectrochemical sensor based on light-excited nanozymes, the steps are as follows:

[0065] (1) 100 mg of 2-aminoterephthalic acid was added to the polytetrafluoroethylene liner of a high-pressure reactor, and then 100 mL of dimethylformamide and 40 mL of methanol were added and ultrasonically dissolved; then 1000 μL of isopropyl titanate was added, and the mixture was quickly stirred until it became a paste, and then transferred to a high-pressure reactor and reacted at 200° C. for 6 h. Then, the reactant was first soaked in dimethylformamide for 15 h, washed with ethanol, and centrifuged. Then, it was washed with a mixed solution of water and ethanol and centrifuged again. Finally, it was washed with water twice, centrifuged, and dried to obtain a titanium metal organic framework compound.

[0066] (2) 500 mg of titanium metal organic framework compound was added to the polytetrafluoroethylene liner of the autoclave, 60 mL of dimethylformamide and 20 mL of water were added, and ultrasonic treatment was performed until complete dissolution. Then, the autoclave was reacted at 200 °C for 12 h. Then, the reactant was centrifuged 3 times with a mixed solution of water and ethanol, and then washed with water and centrifuged 3 times; then, it was dried at 100 °C under vacuum conditions for 5 h to obtain the product, namely carbon-doped TiO2.

[0067] (3) 400 mg of carbon-doped TiO2, 100 mg of norfloxacin, 150 mg of methacrylamide, and 90 mL of ethanol were added to a beaker in sequence, and then ultrasonicated until completely dissolved, followed by stirring for 20 h for prepolymerization, and then 200 μL of ethylene glycol dimethacrylate and 80 mg of 2,2′-azobisisobutyronitrile were added, stirred for 50 min, and placed in a water bath at 80°C. After constant temperature heating for 12 h, the mixture was washed with ethanol and centrifuged, and then dried in a vacuum drying oven at 80°C for 6 h to obtain a carbon-doped TiO2 / molecular imprinting polymer film-norfloxacin.

[0068] (4) The carbon-doped TiO2 / molecularly imprinted polymer membrane-norfloxacin was placed in a 0.25 mol / L sodium hydroxide solution and eluted for 10 min. After eluting norfloxacin, the carbon-doped TiO2 / molecularly imprinted polymer membrane was obtained.

[0069] (5) A 15 mg / mL carbon-doped TiO2 / molecularly imprinted polymer film dispersion was prepared with water as a dispersant, and 400 μL of the carbon-doped TiO2 / molecularly imprinted polymer film dispersion, 400 μL of ethanol, and 200 μL of a 10 wt% perfluororesin solution were mixed and dispersed evenly by ultrasonication to obtain a mixed dispersion; 20 μL of the mixed dispersion was dropwise applied to the surface of a clean L-shaped glassy carbon electrode (with a diameter of 3 mm and an electrode head length of 5 mm), and after drying, a carbon-doped TiO2 / molecularly imprinted polymer film modified glassy carbon electrode was obtained, which was a molecularly imprinted photoelectrochemical sensor based on light-excited nanozymes for the determination of norfloxacin.

[0070] Example 2

[0071] A preparation of a molecularly imprinted photoelectrochemical sensor based on light-excited nanozymes, the steps are as follows:

[0072] (1) 1256 mg of 2-aminoterephthalic acid was added to the polytetrafluoroethylene liner of an autoclave, and then 150 mL of dimethylformamide and 50 mL of methanol were added and ultrasonically dissolved; then 1500 μL of isopropyl titanate was added, and the mixture was quickly stirred until it became a paste, and then transferred to an autoclave for reaction at 180° C. for 12 h. Then, the reactant was first soaked in dimethylformamide for 40 h, washed with ethanol, and centrifuged. Then, the reactant was washed with a mixed solution of water and ethanol and then centrifuged. Finally, the mixture was washed with water twice, centrifuged, and dried to obtain a titanium metal organic framework compound.

[0073] (2) 600 mg of titanium metal organic framework compound was added to the polytetrafluoroethylene liner of the autoclave, 75 mL of dimethylformamide and 25 mL of water were added, and ultrasonic treatment was performed until completely dissolved. The autoclave was then reacted at 180°C for 20 h. The reactant was then centrifuged three times with a mixed solution of water and ethanol, and then washed with water and centrifuged three times. The product was then dried at 150°C under vacuum conditions for 3 h to obtain the product, i.e., carbon-doped TiO2.

[0074] (3) 500 mg of carbon-doped TiO2, 120 mg of norfloxacin, 180 mg of methacrylamide, and 100 mL of ethanol were added to a beaker in sequence, and then ultrasonicated until completely dissolved, followed by stirring for 40 h for prepolymerization, and then 300 μL of ethylene glycol dimethacrylate and 100 mg of 2,2′-azobisisobutyronitrile were added. After stirring for 50 min, the mixture was placed in a water bath at 85°C and heated at a constant temperature for 10 h. The mixture was washed with ethanol and centrifuged, and then dried in a vacuum drying oven at 100°C for 5 h to obtain a carbon-doped TiO2 / molecular imprinting polymer film-norfloxacin.

[0075] (4) The carbon-doped TiO2 / molecularly imprinted polymer membrane-norfloxacin was placed in a 0.20 mol / L sodium hydroxide solution and eluted for 10 min. After eluting norfloxacin, the carbon-doped TiO2 / molecularly imprinted polymer membrane was obtained.

[0076] (5) A 20 mg / mL carbon-doped TiO2 / molecularly imprinted polymer film dispersion was prepared with water as a dispersant, and 50 μL of the carbon-doped TiO2 / molecularly imprinted polymer film dispersion, 500 μL of ethanol, and 100 μL of a 5 wt% perfluororesin solution were mixed and ultrasonically dispersed to obtain a mixed dispersion; 5 μL of the mixed dispersion was dropwise applied to the surface of a clean L-shaped glassy carbon electrode (with a diameter of 3 mm and an electrode head length of 5 mm), and after drying, a carbon-doped TiO2 / molecularly imprinted polymer film modified glassy carbon electrode was obtained, which was a molecularly imprinted photoelectrochemical sensor based on light-excited nanozymes for the determination of norfloxacin.

[0077] Example 3

[0078] A preparation of a molecularly imprinted photoelectrochemical sensor based on light-excited nanozymes, the steps are as follows:

[0079] (1) 1068 mg of 2-aminoterephthalic acid was added to the polytetrafluoroethylene liner of the autoclave, and then 18 mL of dimethylformamide and 2 mL of methanol were added and ultrasonically dissolved; then 960 μL of isopropyl titanate was added, and the mixture was quickly stirred until it became a paste, and then transferred to the autoclave and reacted at 150° C. for 24 h. Then, the reactant was first soaked in dimethylformamide for 12 h, washed with ethanol, and centrifuged. Then, it was washed with a mixed solution of water and ethanol and centrifuged again. Finally, it was washed with water twice, centrifuged, and dried to obtain a titanium metal organic framework compound.

[0080] (2) 420 mg of titanium metal organic framework compound was added to the polytetrafluoroethylene liner of the autoclave, 15 mL of dimethylformamide and 3 mL of water were added, and ultrasonic treatment was performed until completely dissolved, and then the reaction was carried out in the autoclave at 150°C for 48 h, and then the reactant was centrifuged 3 times with a mixed solution of water and ethanol, and then washed with water and centrifuged 3 times; then dried under vacuum conditions at 60°C for 6 h to obtain the product, i.e., carbon-doped TiO2. The other conditions of this step remained unchanged, and the reaction time at 150°C in the autoclave was changed to 12 h, 24 h, 36 h, 60 h, and 72 h, respectively, to obtain 6 carbon-doped TiO2 with different hydrolysis times.

[0081] (3) 100 mg of carbon-doped TiO2 (carbon-doped TiO2 obtained by hydrolysis for 48 h in step (2)), 35 mg of norfloxacin, 75 mg of methacrylamide, and 25 mL of ethanol were added to a beaker in sequence, and then ultrasonicated until completely dissolved, followed by stirring for 12 h for prepolymerization, and then 90 μL of ethylene glycol dimethacrylate and 30 mg of 2,2′-azobisisobutyronitrile were added. After stirring for 30 min, the mixture was placed in a 60°C water bath and heated at a constant temperature for 24 h. The mixture was washed with ethanol and centrifuged, and then dried in a 60°C vacuum drying oven for 8 h to obtain a carbon-doped TiO2 / molecular imprinting polymer film-norfloxacin.

[0082] (4) The carbon-doped TiO2 / molecularly imprinted polymer membrane-norfloxacin was placed in a 0.10 mol / L sodium hydroxide solution and eluted for 30 min. After eluting norfloxacin, the carbon-doped TiO2 / molecularly imprinted polymer membrane was obtained.

[0083] (5) A 10 mg / mL carbon-doped TiO2 / molecularly imprinted polymer film dispersion was prepared with water as a dispersant, and 250 μL of the carbon-doped TiO2 / molecularly imprinted polymer film dispersion, 250 μL of ethanol, and 60 μL of a 5 wt% perfluororesin solution were mixed and ultrasonically dispersed to obtain a mixed dispersion; 4 μL of the mixed dispersion was dropwise applied to the surface of a clean L-shaped glassy carbon electrode (with a diameter of 3 mm and an electrode head length of 5 mm), and after drying, a carbon-doped TiO2 / molecularly imprinted polymer film modified glassy carbon electrode was obtained, which was a molecularly imprinted photoelectrochemical sensor based on light-excited nanozymes for the determination of norfloxacin.

[0084] Test Example 1

[0085] The titanium metal organic framework compound prepared in step (1) of Example 3 and the carbon-doped TiO2 obtained by hydrolyzing the titanium metal organic framework compound in step (2) for different times were characterized by scanning electron microscopy and energy spectrum.

[0086] Figure 2 The scanning electron microscope images of titanium metal organic framework compounds and carbon-doped TiO2 with different hydrolysis times, among which A is titanium metal organic framework compound (i.e., hydrolysis time is 0h); B is carbon-doped TiO2 with hydrolysis time of 12h; C is carbon-doped TiO2 with hydrolysis time of 24h; D is carbon-doped TiO2 with hydrolysis time of 36h; E is carbon-doped TiO2 with hydrolysis time of 48h; F is carbon-doped TiO2 with hydrolysis time of 60h. It can be clearly seen from A that the synthesized titanium metal organic framework compound is evenly distributed, showing a particle structure with a size of about 300-500nm. It can be seen from BF that compared with the titanium metal organic framework, the particles become smaller and smaller with the extension of hydrolysis time, and when the hydrolysis time is 60h, the small particles of carbon-doped TiO2 are obviously agglomerated.

[0087] The energy spectrum of carbon-doped TiO2 with a hydrolysis time of 48h is shown in Figure 3 As shown, A is the total element distribution diagram of C, O and Ti; B is the element distribution diagram of C; C is the element distribution diagram of O; D is the element distribution diagram of Ti; Figure 3 It can be seen that C, O and Ti elements are distributed in the material.

[0088] Test Example 2

[0089] The carbon-doped TiO2 obtained in step (2) of Example 3 with a hydrolysis time of 48 h was characterized by X-ray diffraction and X-ray photoelectron spectroscopy.

[0090] X-ray diffraction characterization of carbon-doped TiO2 Figure 4 (with standard TiO2 as reference), from Figure 4It can be seen that the highest intensity diffraction peak of standard TiO2 (commercial standard TiO2) 2θ = 25.3° corresponds to the (101) crystal plane, and the other four strong diffraction peaks 2θ = 37.9°, 48.1°, 53.8° and 62.8° correspond to the (103), (004), (112), (200) crystal planes, which are consistent with the standard diffraction card of TiO2 anatase. The highest intensity diffraction peak of carbon-doped TiO2 is 2θ = 25.2°, and the other four diffraction peaks are 2θ = 37.8°, 48°, 54° and 62.9°. Compared with the characteristic diffraction peak of standard TiO2, the position of the characteristic peak of carbon-doped TiO2 has shifted, indicating that the doping of C has caused the crystal lattice of TiO2 to be distorted.

[0091] X-ray photoelectron spectroscopy characterization of carbon-doped TiO2 Figure 5 , where A is the full spectrum of carbon-doped TiO2, from which it can be seen that the sample only contains C, O, and Ti elements, indicating that the material was successfully prepared; B is the high-resolution spectrum of C1s in carbon-doped TiO2, with two main peaks at 284.68eV and 288.31eV, respectively. The peak at 284.68eV is related to hydrocarbons, and the peak at 288.31eV is due to the presence of CO-Ti bonds in the sample; C is the high-resolution spectrum of O1s in carbon-doped TiO2, compared with the binding energy of O1s of pure TiO2 in the reference literature of 529.6eV and 530.90eV, the binding energy of O1s after doping moves to 529.81eV and 531.43eV, indicating that the doping of C causes the distortion of the TiO2 lattice; D is the high-resolution spectrum of Ti2p in carbon-doped TiO2, Ti2p 3 / 2 and Ti2p 1 / 2 The binding energies are 458.5eV and 464.27eV, respectively. Compared with pure TiO2, both are shifted, indicating that the incorporation of C into the TiO2 matrix leads to the distortion of the TiO2 lattice.

[0092] Test Example 3

[0093] The titanium metal organic framework compound prepared in step (1) of Example 3 and the carbon-doped TiO2 obtained by hydrolyzing the titanium metal organic framework compound in step (2) for different times were tested for the performance of light-excited nanozymes.

[0094] Nanozymes with photoexcitable peroxidase-like catalytic activity can catalyze the oxidation of 3,3′,5,5′-tetramethylbenzidine to produce a color reaction under light conditions, that is, the color-developing substance 3,3′,5,5′-tetramethylbenzidine is oxidized into a blue product (with a characteristic absorption peak at about 652nm). A dispersion containing 0.20mmol / L 3,3′,5,5′-tetramethylbenzidine color developer and 26μg / mL titanium metal organic framework or carbon-doped TiO2 formed in a 0.2mol / L acetic acid-sodium acetate base solution at pH 4.6 was irradiated with visible light (>400nm) for 15min, and finally the visible light absorption spectrum was tested in the range of 400-800nm, and the visible light absorption spectrum test was directly performed without irradiation under visible light for 15min as a control. Comparison of the performance of photoexcitable nanozymes of titanium metal organic framework compounds and carbon-doped TiO2 obtained by hydrolyzing titanium metal organic framework compounds for 48h Figure 6 As shown, A is the UV-visible spectrum of the titanium metal organic framework tested after illumination; B is the UV-visible spectrum of the titanium metal organic framework tested directly without illumination; C is the UV-visible spectrum of carbon-doped TiO2 tested after illumination; D is the UV-visible spectrum of carbon-doped TiO2 tested directly without illumination; E is the UV-visible spectrum of the color-developing substance 3,3,5,5-tetramethylbenzidine tested after illumination. Figure 6 As can be seen in the figure, the catalytic performance of nanozymes of titanium metal organic framework and carbon-doped TiO2 in the absence of light can be basically ignored (B and D). After illumination, both of them show obvious peroxide nanozyme catalytic performance (A and C), and the catalytic performance of carbon-doped TiO2 is the best. In addition, when only the color developer 3,3',5,5'-tetramethylbenzidine is present, no peroxide nanozyme catalytic performance is shown under light conditions (E). Figure 7 The performance of the photoexcited nanozymes (after illumination) of carbon-doped TiO2 obtained by hydrolysis of titanium metal organic framework compounds at different times is compared. It can be seen that the catalytic performance of carbon-doped TiO2 with a hydrolysis time of 48h is the best.

[0095] Application Example 1

[0096] The molecular imprinting photoelectrochemical sensor based on light-excited nanozyme obtained in step (5) of Example 3 was used for the photoelectrochemical test of norfloxacin.

[0097] Test method: A molecular imprinting photoelectrochemical sensor based on light-excited nanozymes was used as the working electrode, the reference electrode was an Ag / AgCl electrode, and the auxiliary electrode was a platinum electrode to construct a three-electrode system; the base solution was a mixed aqueous solution containing 1.8 mmol / L hydroquinone (HQ) and 0.1 mol / L sodium sulfate.

[0098] Test conditions: The light source is a 500W xenon lamp, the wavelength of the light source is ≥400nm, the light on-light off interval is 10s, and the potential is -0.2V.

[0099] The molecular imprinting photoelectrochemical sensor based on light-excited nanozyme was incubated in different concentrations of norfloxacin solution at 25°C for 50 min and then tested for its photocurrent response in the test base solution. The measurement results are shown in Figure 8 and Fig. 9 .

[0100] Figure 8 The photocurrent response diagram of the molecular imprinting photoelectrochemical sensor based on light-excited nanozymes to different concentrations of norfloxacin, where A is before incubation with norfloxacin; B is after incubation with 1.0g / L norfloxacin; C is after incubation with 5.0g / L norfloxacin; D is after incubation with 10.0g / L norfloxacin; E is after incubation with 20.0g / L norfloxacin; F is after incubation with 30.0g / L norfloxacin; G is after incubation with 40.0g / L norfloxacin; H is after incubation with 50.0g / L norfloxacin. Figure 8 It can be seen that as the concentration of norfloxacin increases, the photocurrent gradually decreases. This is because the higher the concentration of the target molecule norfloxacin, the more it combines with the holes. The fewer holes there are, the greater the obstacle to electron transfer, resulting in a decrease in photocurrent.

[0101] Fig. 9 This is the calibration curve (i.e., working curve) of the photocurrent response of the molecular imprinting photoelectrochemical sensor based on light-excited nanozymes to norfloxacin. According to the calibration curve, the linear range of the molecular imprinting photoelectrochemical sensor for determining norfloxacin is 1.0-50.0 μg / L, the linear equation is I(μA)=-4.09681-1.249lgc(c:g / L), and the detection limit is 0.014 μg / L.

[0102] Application Example 2

[0103] The molecular imprinting photoelectrochemical sensor based on light-excited nanozymes obtained in step (5) of Example 3 was used for mechanism exploration. Hydroxylamine hydrochloride (to remove O2 · ), thiourea (scavenges ·OH), tryptophan (scavenges 1 O2) and ethanol (to remove h + ) and other chemical scavengers to explore the types of active substances produced during the illumination process.

[0104] Test method: A three-electrode system was constructed using a molecular imprinting photoelectrochemical sensor based on light-excited nanozymes as the working electrode, an Ag / AgCl electrode as the reference electrode, and a platinum electrode as the auxiliary electrode; the base solutions were a mixed aqueous solution containing 1.8mmol / L HQ + 0.1mol / L sodium sulfate, a mixed aqueous solution of 1.8mmol / L HQ + 0.1mol / L sodium sulfate + 0.1mmol / L hydroxylamine hydrochloride, a mixed aqueous solution of 1.8mmol / L HQ + 0.1mol / L sodium sulfate + 0.1mmol / L tryptophan, a mixed aqueous solution of 1.8mmol / L HQ + 0.1mol / L sodium sulfate + 0.1mmol / L ethanol, and a mixed aqueous solution of 1.8mmol / L HQ + 0.1mol / L sodium sulfate + 0.1mmol / L thiourea.

[0105] Test conditions: The light source is a 500W xenon lamp, the wavelength of the light source is ≥400nm, the light on-light off interval is 10s, and the potential is -0.2V.

[0106] The photocurrent response of molecular imprinted photoelectrochemical sensor was tested in different substrate solutions.

[0107] Fig.10 The mechanism exploration process and results of molecular imprinting photoelectrochemical sensor, where A is a 1.8 mmol L - 1 HQ and 0.1 mol L -1 A is the photocurrent diagram of a mixed aqueous solution of sodium sulfate; B is the photocurrent diagram of adding 0.1mmol / L hydroxylamine hydrochloride to A; C is the photocurrent diagram of adding 0.1mmol / L tryptophan to A; D is the photocurrent diagram of adding 0.1mmol / L ethanol to A; E is the photocurrent diagram of adding 0.1mmol / L thiourea to A. Fig.10 It can be seen that the photocurrent after adding hydroxylamine hydrochloride and tryptophan did not change significantly compared with the blank. When ethanol and thiourea were added, the photocurrent dropped sharply, indicating that the photocurrent -1 HQ and 0.1 mol L -1 The active substance that plays an oxidative role in the sodium sulfate solution system is h + and OH.

[0108] In order to verify whether dissolved oxygen in the solution participates in the photoelectrochemical reaction, the -1 HQ and 0.1 molL -1 The photocurrent changes of the mixed aqueous solution of sodium sulfate before and after deoxygenation are as follows Fig.11 As shown, from Fig.11It can be seen that the photocurrent before and after deoxygenation has basically not changed, indicating that the oxygen in the solution does not participate in the photoelectrochemical reaction process. Based on the above experiments, the detection mechanism of molecular imprinting photoelectrochemical sensors was proposed, such as Fig.12 shown.

[0109] from Fig.12 It can be seen that after the molecular imprinting photoelectrochemical sensor is excited by light, the electrons on the valence band of carbon-doped TiO2 jump to the conduction band, and holes appear in the valence band after losing electrons. The holes react with H2O in the electrolyte to produce ·OH, and ·OH and holes oxidize hydroquinone in the electrolyte to benzoquinone. Benzoquinone obtains electrons from the conduction band to regenerate hydroquinone, and the electrons on the base electrode transfer to the holes in the carbon-doped TiO2 to form a photocurrent. When the holes in the molecular imprinting film are occupied by norfloxacin molecules, hydroquinone in the solution is inhibited from participating in the reaction, resulting in a decrease in the photocurrent.

[0110] The embodiments described are only descriptions of the preferred modes of the present invention and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a molecularly imprinted photoelectrochemical sensor based on light-excited nanozymes, characterized in that: The following steps are involved: Using isopropyl titanate as a titanium source and 2-aminoterephthalic acid as a ligand, a titanium metal organic framework compound is synthesized; the titanium metal organic framework compound is subjected to low-temperature hydrolysis to obtain carbon-doped TiO2; using the carbon-doped TiO2 and template molecules to prepare a carbon-doped TiO2 / molecularly imprinted polymer film through chemical polymerization; fixing the carbon-doped TiO2 / molecularly imprinted polymer film to the surface of a base electrode to obtain the molecularly imprinted photoelectrochemical sensor based on light-excited nanozymes; The temperature of the low-temperature hydrolysis is 50-200°C, and the time is 10-72h; the low-temperature hydrolysis is carried out in a mixed solution of dimethylformamide and water; The method of preparing a carbon-doped TiO2 / molecular imprinting polymerization membrane by chemical polymerization using carbon-doped TiO2 and template molecules comprises: mixing carbon-doped TiO2, template molecules, methacrylamide and ethanol, ultrasonicating until completely dissolved, prepolymerizing for 5-40 hours, then adding ethylene glycol dimethacrylate and 2,2′-azobisisobutyronitrile, stirring for 10-60 minutes and reacting at 30-85°C for 10-40 hours, washing, drying and eluting in a sodium hydroxide solution for 5-90 minutes after the reaction to obtain the carbon-doped TiO2 / molecular imprinting polymerization membrane; the amount ratio of the carbon-doped TiO2, template molecules, methacrylamide, ethanol, ethylene glycol dimethacrylate and 2,2′-azobisisobutyronitrile is 20-500 mg: 10-120 mg: 10-200 mg: 10-100 mL: 20-300 μL: 10-100 mg.

2. The preparation method according to claim 1, characterized in that The method for synthesizing a titanium metal organic framework compound using isopropyl titanate as a titanium source and 2-aminoterephthalic acid as a ligand comprises: mixing 2-aminoterephthalic acid, dimethylformamide, methanol and isopropyl titanate, reacting at 60-250° C. for 5-50 hours, soaking the reactants in dimethylformamide for 6-40 hours after the reaction, and then washing and drying to obtain the titanium metal organic framework compound; the dosage ratio of the 2-aminoterephthalic acid, dimethylformamide, methanol and isopropyl titanate is 20-1500 mg: 5-150 mL: 0.5-50 mL: 50-1500 μL.

3. The preparation method according to claim 1, characterized in that: The carbon-doped TiO2 / molecular imprinting polymer film is fixed to the surface of the base electrode to obtain the molecular imprinting photoelectrochemical sensor based on light-excited nanozyme, including: dispersing the carbon-doped TiO2 / molecular imprinting polymer film in water to obtain a carbon-doped TiO2 / molecular imprinting polymer film dispersion; mixing the carbon-doped TiO2 / molecular imprinting polymer film dispersion with ethanol and perfluororesin solution to obtain a mixed dispersion; drop-coating the mixed dispersion on the surface of the base electrode, and after drying, obtaining a base electrode modified with the carbon-doped TiO2 / molecular imprinting polymer film, which is the molecular imprinting photoelectrochemical sensor based on light-excited nanozyme.

4. The preparation method according to claim 3, characterized in that: The concentration of the carbon-doped TiO2 / molecularly imprinted polymer membrane dispersion is 2-20 mg / mL; the concentration of the perfluororesin solution is 1-10 wt %; the volume ratio of the carbon-doped TiO2 / molecularly imprinted polymer membrane dispersion, ethanol and perfluororesin solution is 50-500:50-500:10-200.

5. The preparation method according to claim 1, characterized in that: The template molecule is norfloxacin.

6. A molecularly imprinted photoelectrochemical sensor based on light-excited nanozyme prepared by the preparation method as described in claim 5.

7. The use of the molecularly imprinted photoelectrochemical sensor based on light-excited nanozymes in detecting norfloxacin as claimed in claim 6, characterized in that: The molecular imprinting photoelectrochemical sensor based on light-excited nanozyme is used as a working electrode, an Ag / AgCl electrode is used as a reference electrode, and a platinum electrode is used as an auxiliary electrode to form a three-electrode system to achieve photoelectrochemical detection of norfloxacin; The base solution of the three-electrode system is a mixed aqueous solution containing 1.8 mmol / L hydroquinone and 0.1 mol / L sodium sulfate solution.

Citation Information

Patent Citations

  • Molecular imprinting photoelectrochemical sensor as well as preparation method and application thereof

    CN111272857A

  • Preparation method of alpha-TiO2at-NH2-MIL-125 composite photocatalytic material

    CN114632549A

  • Self-cleaning photoelectrochemical sensor based on signal polarity overturning

    CN117907392A